A Set of Proposed Indicators for the LGBTI Inclusion Index - Badgett, M.V. Lee; Sell, Randall (United Nations Development Programme, New York, 2018)
This publication provides the background for a set of proposed indicators for a global index to measure the inclusion of LGBTI people. These indicators represent the most recent step in the development of the LGBTI Inclusion Index. The acronym LGBTI refers to lesbian, gay, bisexual, transgender, and intersex people. It is very difficult to define terms related to sexual orientation, gender identity or expression, and sex characteristics (SOGIESC) across diverse cultural and national contexts. We use the collective term “LGBTI people” because they are a diverse group that nevertheless faces some common challenges: stigma, discrimination, and violence because of their sexual orientation, gender identity or expression, and sex characteristics. This definition is neither exclusive nor final; other concepts, terms, or identities may be relevant in different settings, and conceptions may evolve over time. Inclusion of LGBTI people is imperative if we are to deliver on the pledge of the 2030 Agenda for Sustainable Development to leave no one behind. The principles of leaving no one behind and reaching the furthest behind first permeate the 2018-2021 Strategic Plan of the United Nations Development Programme (UNDP), as well as the 2016-2021 UNDP HIV, Health and Development Strategy. The process of creating the LGBTI Inclusion Index began in 2015, when UNDP, in partnership with the Office of the High Commissioner for Human Rights (OHCHR), convened meetings with a multi-sectoral group of experts and with representatives from civil society to discuss the development of an index. In addition to confirming the viability and desirability of such an Index, the 2015 consultation resulted in two key aspects of an index: an agreement about the working definition of inclusion for purposes of the Index, and an agreement about dimensions of human freedom that should be included and measured by such an index.